Effects of N and K Concentrations on Nutrient Uptake, Photosynthetic Capacity and Growth of Bell Pepper (Capsicum Annuum Var. Grossum) Grown Under Rain Shelters in the Lowlands - Ahmad, Norhanani (2009)
Effects of different concentrations of N and K in the nutrient solutions on nutrient uptake, photosynthetic capacity and growth of bell pepper (Capsicum annuum var. grossum) cv. „Canape‟ under rainshelters in the lowland were evaluated. This study was carried out under rainshelter in randomized complete block design (RCBD) with three replications from February until July 2005 at Institut Latihan Pertanian Ayer Hitam (IPAH), Johor. Bell pepper plants were grown in 9L pots containing cocoa peat and burnt rice husk at 1:1. Except for N and K concentrations, a complete nutrient solution based on the Cooper nutrient formulation was supplied using fertigation system. The concentrations of N:K at 250:350 mgL-1=S1, 250:300 mgL-1=S2, and 200:300 mgL-1=S3 were applied from the first to 124 day after transplanting (DAT). The percentage of leaf N, P, K, Ca and Mg concentration, nutrient uptake and leaf gas exchange were measured at 7, 38 and 124 DAT. Plant height, stem diameter and leaf area index were measured at 7 (vegetative stage), 14 (early reproductive stage), 21, 28, 38 (first fruiting stage) and 124 days after transplanting (DAT). Total leaf area, leaf, stem and root dry weight at 7, 14, 28, 38 and 124 DAT. While, flower and fruit dry weights were measured start at 14, 28, 38 and 124 DAT. Results showing significant differences were observed in percentage of leaf N, P, K at vegetative stage and Mg concentration at fruiting stage. This showed that the N and K concentrations in the nutrient solution influenced the nutrients uptake and accumulated in the plants leaf. Higher total of K followed by N, Ca, and P and Mg uptake showed the importance of N and K for bell pepper growth. Higher maximum assimilation rate of photosynthesis (Amax), net photosynthesis (PN) and transpiration rate (E) at vegetative stage in 250:350 mgL-1 of N:K indicated that the photosynthetic capacity would increase with higher N and K concentration. Lower of Fv/Fm ratio at 7 DAT in all treatments indicated that the plants were under short term environmental stress. However, this condition was improved at 38 and 124 DAT. Plant growth especially plant height, stem diameter, total leaf area, fruit weight and number of fruits per plant increased with the increasing of N and K concentration in the nutrient solution. These indicated the importance of N and K in increasing the growth of bell pepper.